2012
DOI: 10.3171/2012.2.jns11714
|View full text |Cite
|
Sign up to set email alerts
|

Targeted delivery of nerve growth factor via encapsulated cell biodelivery in Alzheimer disease: a technology platform for restorative neurosurgery

Abstract: With refinement, the ECB technology is positioned to become an important therapeutic platform in restorative neurosurgery and, in combination with other therapeutic factors, may be relevant for the treatment of a variety of neurological disorders. Clinical trial registration no.: NCT01163825.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(77 citation statements)
references
References 17 publications
0
74
0
1
Order By: Relevance
“…A rodent model study showed that application of highfrequency stimulation to isolated hippocampal slices significantly increased synaptic plasticity in the CA1 region and promoted a twofold increase of non-amyloidogenic α-secretase activity. Neuroimaging studies in AD have demonstrated widespread structural and metabolic abnormalities, principally in areas associated with memory functions [33]. As recent data suggest system-level defects characterized by alterations in memory circuits, it is reasonable to expect that external stimulation of subareas within the circuitry will ameliorate symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A rodent model study showed that application of highfrequency stimulation to isolated hippocampal slices significantly increased synaptic plasticity in the CA1 region and promoted a twofold increase of non-amyloidogenic α-secretase activity. Neuroimaging studies in AD have demonstrated widespread structural and metabolic abnormalities, principally in areas associated with memory functions [33]. As recent data suggest system-level defects characterized by alterations in memory circuits, it is reasonable to expect that external stimulation of subareas within the circuitry will ameliorate symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…DBS of the nucleus basalis of Meynert (NBM) should improve or stabilize memory and cognitive functioning in patients with AD. The hypothesized mechanism involves a facilitation of neural oscillations and the synthesis of NGFs [33]. Medial temporal structures, including the hippocampus and the entorhinal cortex, have long been known to be important in memory formation and recall [25].…”
Section: Discussionmentioning
confidence: 99%
“…Conceptually, cells are immunoisolated from the host system by being encapsulated in a porous membrane through which nutrients, metabolic by-products and secreted factors diffuse whereas immune cells do not. While encapsulated cell therapy is an active field and it has been investigated clinically [185,228], there remains an immune response as the encapsulated cells are subject to antigen shedding [93].…”
Section: Challenges Faced In Cell-based Strategies For Regenerative Smentioning
confidence: 99%
“…Aquesta estratègia s'ha utilitzat des de fa temps per a malalties com ara l'Alzheimer (Wahlberg i altres, 2012). Tot i que aquestes estratègies són prometedores, encara ens queden per superar problemes com són la distribució limitada dels factors o bé la impossibilitat de regenerar neurones perdudes quan la degeneració és avançada.…”
Section: Trasplantament De Cèl·lules Encapsulades Alliberadores De Faunclassified